Cementation of Sand With Enzyme-Induced Carbonate Precipitation (EICP) Using Concrete-Extracted Calcium - He, Jia; Mao, Xunyu; Zhou, Yundong; Tang, Qiang (Frontiers in Physics, 2022)
Calcium carbonate precipitation and crystallization induced by urease enzyme to solidify soil is known as biocement technology. The uses of waste and cheap materials can make this technology more cost-effective and practical for applications. In this study, calcium ions were obtained by dissolving waste concretes in acidic liquid. Sand columns were treated by the enzyme induced carbonate precipitation (EICP) with either concrete extracted calcium or reagent calcium for comparison. Compressive strengths, calcium carbonate contents and microscopic analysis on the treated sand were carried out. It was found that the compressive strength of the former could reach 833 kPa in dry state and 204 kPa in wet state after 5 times of EICP treatments, both of which were higher than that of the latter. The calcium carbonate contents could reach 2%-3% after 3 to 5 times of treatments. Based on the scanning electron microscope (SEM) and X-ray diffractometer (XRD) analysis, the crystal type of calcium carbonate produced in sand was calcite. The comparative results showed that the treatment effects using concrete extracted calcium was similar or better than that using reagent calcium.